Effect of Arsenic Coordination State on the Structure, Aromaticity, and Optical Properties of Dithieno[3, 2‐b:2′, 3′‐d]arsoles. Issue 11 (21st December 2018) - Green, Joshua P.; Gupta, Arvind K.; Orthaber, Andreas
Abstract : A silylated derivative of 4‐phenyl‐dithieno[3, 2‐ b :2′, 3′‐ d ]arsole (DTAs) was synthesized, and the effect of coordinating of DTAs compounds to Pd on their structural and optical properties was investigated. Coordination of the As to Pd was found to increase the structural aromaticity of the ring system as measured by the harmonic oscillator measure of heterocyclic electron delocalization (HOMHED), and the pyramidalization of the As atoms was also found to show a good correlation with the HOMHED values. However, coordination had a more subtle impact on the optical properties than seen for phosphorus‐containing analogues as the metal‐ligand interactions were weaker. Abstract : The optical and structural effects of substituting dithienoarsole with silyl substituents were investigated. Silylation improved solubility sufficiently to allow a Pd complex of dithienoarsole to be obtained and characterized, and the optical properties of this complex are reported.